An alternative synthetic approach for 1,3- benzoxazine derivatives - A. U G/Gabbas,; Mohammed, Issam Ahmed; Ahmad @ Ayob, Mansor (International Journal of Scientific & Technology Research, 2014)
1,3-benzoxazine derivatives were synthesized in high yield using three-step synthetic technique by the condensation of 2-hydroxybenzaldehyde with aromatic amines, reducing the condensation products and replacing the usual formaldehyde with methylene bromide to achieve ring closure. The structures of the benzoxazines were confirmed by FTIR, 1H and 13C NMR spectra and Mass spectroscopy.